Recycle and Reuse Car Wash Water Using Natural Coagulants - Mrs. Sathiya Priya; Chandru. S; Gokula Prasanth. R; Krishnaa Dev. A; Laknesh. N (International Journal of Scientific Research in Civil Engineering, 2022)
People used to wash their automobiles in the backyards of their houses or other convenient locations in the past. People later wash their automobiles at hand wash car washes. Mechanical devices now do this function. In each scenario, the water used to clean the automobile becomes contaminated. If wash water is drained into storm drains, it eventually finds its way into rivers and streams, where it has an impact on aquatic life. If it’s drained into sewers, it mixes with sewage, which includes a lot of pollutants and germs, increasing the burden on the sewage treatment facility. As a result, it is required to build a separate water treatment facility at vehicle wash centres, which will reduce the load of sewage water treatment. The installation of vehicle wash centres is a technological advancement. Technology advancements may occasionally have a harmful influence on the environment. The use of a water recycling system in a vehicle wash reduces the amount of fresh water used. As a result, vehicle wash water must be recycled and reused in order to save natural resources. After appropriate treatment, the water treatment facility at car wash centres is obliged to use the waste water obtained from a vehicle wash for washing the next automobile that comes around.